Microbiological safety of artisanal corn dougth expended in Puerto La Cruz, Venezuela - Alessi-Cusati, Próspero A. (2020)
Recently, artisanal masses of pilar corn have become a food for mass consumption in Venezuela, without adequate sanitary control in terms of production and sale. There are very few internationally referenced studies and none recently locally, regarding this product; for this reason, the objective of this research has focused on its microbiological evaluation with samples obtained in the municipal market of Puerto La Cruz, which are the main point of sale of the same in the main Venezuelan cities. The frequencies of total coliforms, fecal coliforms, presence of Escherichia coli, aerobic mesophiles and Staphylococcus aureus were determined as indicators of inadequate manipulation; The presence of molds and yeasts was also considered as microorganisms associated with cereals. It is concluded that all the samples of pillared corn masses present a high level of these indicator microorganisms and that their consumption without proper cooking could carry significant health risks.